The Effects of Work Stress Towards Turnover Intention Mediated by Burnout: Study on Employees Working in PT Mitra Jaya Raya Borneo Pontianak - Hugo Fostin Hokianto; Sunardi Ginting; Sandra Endang Suci Octora (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
One of the corporate responsibilities towards their employees is to maintain the employees working in the company, with the work environment provided, the work load given, and developing them with good training. In reality, employees often experience work stress in doing their jobs, and the accumulation of work stress triggers burnout, thus encouraging them to leave the company. This study examines the effect of job stress on turnover intention mediated by burnout at PT Mitra Jaya Raya Borneo Pontianak as the object of research, with a population of 35 employees. Using saturation sampling technique, the sample of this study was 35 respondents. This research uses PLS-SEM analysis, using the SmartPLS 3.2.9 application to process questionnaires data. The results of this study indicate that job stress has a significant positive effect on turnover intention, job stress has a significant positive effect on burnout, burnout has an insignificant positive effect on turnover intention, and burnout does not mediate the relationship between job stress and turnover intention.